Sabbatical leave report: sabbatical Fall 2013 - Volkman, Richard (2013)
This sabbatical leave was devoted to revising and editing material for a book project with the working title, Meditations on Heroic Individualism. The principle objective was to have a finished manuscript, ready for submission to publishers. Additionally, a proposal was developed to add Special Topics course, Ethical Individualism, as a permanent course.
Keywords: dept.phi; faculty_collection; sabbatical_report